The Use of Piracy Windows among IAIN Palangka Raya Students in Sharia Economic Law Perspective - Sadiani; Wahyunita, Laili; Hermawan, Muhammad Bayu Heksa Putra; Alfionita, Lara; Rahimah, Annisa (International Journal of Law and Public Policy (IJLAPP), 2022)
This research was motivated by the widespread use of pirated windows among students of IAIN Palangka Raya that they get from the service of installing computer shops in the City of Palangka Raya. The legal status of using pirated windows is categorized as ‘urf facade. . But there is tolerance among students of IAIN Palangka Raya who are classified as not being able to obtain original windows, that they may use pirated windows for lecture purposes. This is ḥillah because the origin was banned but used for good. Also due to difficulties if you require to use original windows. Finally, the use of pirated windows can be tolerated. This is in line with the masyaqqah's perspective that the aim is to take rukhs’ah.